Rumen solids as a superior inoculum for in vitro volatile fatty acid production: Effects and metagenomic insights - Yuehan Li; Le Chen; Jiasheng Zhang; Yajie Zhang; Maoqing Wang; Ru Zhang; Wei Fang; Panyue Zhang; Guangming Zhang (Bioresource Technology, 2027)

Insulin-like peptide 3 facilitates sheep oocytes in vitro maturation and subsequent early embryo development - Qi Yang; Rui-Feng Zhang; Zhao-Yu Jiang; Dui Sun; Rui-Hao Tang; Xiao-Yi Zhang; Yi-Tong Li; Wen-Ying Li; Ao Liu; Chun-Lan Zhang; Zhi-Wen Jia; Meng-Lei Feng; et al. (Theriogenology, 2026)

Characterization of hygroscopicity-based mixing state at four sites in China - Jingye Ren; Fang Zhang; Lu Chen; Jieyao Liu; Wei Xu; Honghao Xu; Zhe Wang; Ru-Jin Huang (Journal of Aerosol Science, 2026)

Benzene-modified carbon nitride with enhanced π–π adsorption for efficient lignin C–C bond photocleavage - Yunyi Wang; Ru Yang; Xiang Li; Haiping Wang; Ting Wu; Guigan Fang (Journal of Environmental Chemical Engineering, 2026)

Effects of co-exposure of polyethylene nanoplastics and 6PPD on cardiac function in the early developmental stage of zebrafish - Huan Ru; Chanlin Fang; Yuanxiang Jin (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2026)

Accelerating yeast adaptation: harnessing thermal stress for genomic diversification and thermotolerance in Yarrowia lipolytica - Min He; Ke Zhang; Qian-Xin Hong; Yuan-Chun Fang; Yuan-Ru Xiong; Ye-Ke Wang; Dao-Qiong Zheng (Bioresource Technology, 2026)

Quercetin restores oocyte maturation and embryo development in DEHP-exposed mice via mitochondrial protection and apoptosis inhibition - Dui Sun; Qi Yang; Zhi-Hui Gong; Meng-Lei Feng; Zhi-Wen Jia; Bin-Shuo Yang; Zhao-Yu Jiang; Chun-Ru Song; Fang-Rui Xue; Xiao-Jie Zhang; Hao-Yang Zhang; Chun-Lan Zhang; et al. (Chemico-Biological Interactions, 2026)

Kit Ligand enhances in vitro oocyte maturation and early embryonic development in sheep - Qi Yang; Dui Sun; Zhao-Yu Jiang; Rui-Hao Tang; Rui-Feng Zhang; Xiao-Yi Zhang; Wen-Ying Li; Yi-Tong Li; Ao Liu; Chun-Lan Zhang; Zhi-Wen Jia; Meng-Lei Feng; et al. (Animal Reproduction Science, 2026)

Exploration of Point Load Testing under In Situ Pore Pressure: Mechanical Behaviour and Systematic Characterization - Xin Fang; Cong Li; Ru Zhang; Jianan Li; Zhiqiang He; Jiazhuo Chen; Xiaojun Shi; Heping Xie (Rock Mechanics and Rock Engineering, 2026)

Different mucosal immunity and hormonal responses to routine physical training in the follicular and the luteal phases of elite female athletes - Chung-Kai Wang; Cheng-Shiun He; Ming-Ru Chiang; Pei-Ying Li; Chun-Wei Wang; Liang-You Chen; Shih-Hua Fang (European Journal of Applied Physiology, 2026)

Rubidium isotopes reveal no sub-arc melting of altered oceanic crusts in a cold subduction zone - Zi-Qiang Zhong; Ding-Sheng Jiang; Saskia Erdmann; Yi-Xiang Chen; Xia Hu; Zheng Xu; Wei Zhang; Jia-Ru Sheng; Wang-Ye Li; Fang Huang (Geochimica et Cosmochimica Acta, 2026)

Bioactivity assay coupled with molecular networking for the discovery of antioxidants from purslane - Yan-Xi Li; Mei-Ru Wang; Long-Gao Xiao; Huan Yan; Shan-Shan Ling; Hui Liu; Tao-Bin He; Wei Ni; Xin Fang; Hai-Yang Liu (Food Research International, 2026)

Precision droplet deposition control in helicopter spraying: a novel valve-switch timing method accounting for headwind effects - Shuping Fang; Yu Ru; Ningning Wang; Xiaojun Jin; Chunxia Jiang; Yangyang Liu; Chao Zhang (Computers and Electronics in Agriculture, 2026)

Scenario-based synergistic assessment of crop straw allocation for GHG mitigation and sustainable resource use in China - Yan Ru Fang; Zhongshi Tang; Xuefang Wu; Pingjian Yang (Sustainable Production and Consumption, 2026)

Non-enzymatic electrochemical determination of the food-related biogenic amine serotonin using a reduced graphene oxide/organic–inorganic Copper(I) phosphate composite - Asit Kumar Panda; Tzu-Yuan Sung; Wan-Ju Lu; Yi-Ru Cheng; Wen-Hui Fang; Chih-Min Wang (Food Bioscience, 2026)

Synchronized lignocellulosic pyrolysis for activator-free carbon foams: Role of selective hemicellulose removal - Jia-Cheng Ye; Xiao-Ru Meng; Bo Xia; Ting-Yu Bi; Wei Chen; Lu-jiang Xu; Shuai Gao; Zhen Fang (Journal of Environmental Chemical Engineering, 2026)

Superoxide dismutase/peroxidase-like MoS2 quantum dots enhance ammonia synthesis by Klebsiella pasteurii - Meng-Xin Zhao; Si-Ru Chen; Shan-Shan Hu; Ting-Ting Liu; Jia-Le Teng; Ya-Wen Yu; Jia-Long Zhang; Xue-Ru Zhou; Qun-Feng Ye; Su-Fang Qin; Le-Xing You (Journal of Environmental Chemical Engineering, 2026)

Mask-CDKD: A source-free and label-free cross-domain knowledge distillation framework from SAM for satellite onboard VHR land-cover mapping - Daoyu Shu; Zhan Zhang; Xiao Huang; Ru Wang; Nan Jia; Xinzhe Fu; Bingnan Yang; Fang Wan; Jianzhong Lu; Jianya Gong (ISPRS Journal of Photogrammetry and Remote Sensing, 2026)

Enhancing camptothecin biosynthesis in Camptotheca acuminata through CrLAMT transfer from Catharanthus roseus - Ru Huang; Wen-Hui Ma; Bing-Run Yang; Fang Yu; Ping Kou (Biotechnology Letters, 2026)

Marine microalgae selenium uptake and transformation: Multi-omics insights for sustainable applications - Yimei Xi; Xinjie Wang; Kuo Fang; Ru Chen; Weiming Li; Tingting You; Xiangfeng Zeng; Shaofeng Wang; Yongfeng Jia (Algal Research, 2026)

Accelerating carbon neutrality intensifies trade-offs in China’s energy-water-food nexus - Zhongshi Tang; Tao Wang; Sandylove Afrane; Nihed Benani; Yan Ru Fang; Pingjian Yang (Resources, Conservation and Recycling, 2026)

Overexpression of PtrPYL11 enhance drought tolerance in Populus: evidence from genome-wide identification and comparative transcriptome profiling - Shuang-Lian Deng; Shu-Ying Wei; Rui-Quan Wang; Yuan Zhang; Hao Li; Xing-Yu Liu; Xin-Ran Yu; Guan-Ru Ren; Ting Wang; Fang He (Plant Cell Reports, 2026)

Exploratory analysis of epigenetic dynamics and small extracellular vesicles in Penaeus vannamei hemocytes under inactivated Vibrio parahaemolyticus priming - Yu-Ru Lin; Guan-Lin Lai; Yu-Hsuan Sun; Ta-Jeng Yang; Ting-Yu Huang; Huu-The Nguyen; Muhammad Ar Rozzaaq Nugraha; Novi Rosmala Dewi; Yeh-Fang Hu; Fan-Hua Nan (Journal of Invertebrate Pathology, 2026)

Biovoltage-driven, sulfurized Fe–Co anode promoted the generation of salt source active species for enhanced antibiotic removal - Shengtao Jiang; Jie Fang; Hao Zhou; Xiaojun Wang; Haoyang Liu; Deman Han; Ru Jiang; Yutong Cai; Yiting Shi; Yanbiao Liu (Journal of Environmental Management, 2026)

Flexible and anti-freezing eutectogel for high-performance ionotronic sensors - Ping Gan; Yi-Jun Cao; Ming-Ru Xie; Hui-Ping Chen; Chun-Fang Xie; Jie-Ping Fan (Chemical Engineering Journal, 2026)

Potassium ferrate-coupled endogenous free ammonia enhancing volatile fatty acids production in anaerobic fermentation of concentrated sludge: Insights into efficiency and mechanisms - Qianqian Wang; Xinyu Zhao; Ru Zhang; Yaoxian Hu; Yuping Ye; Wei Fang; Panyue Zhang; Guangming Zhang (Chemical Engineering Journal, 2026)

Short-duration electrical pulse stimulation induces myokines and mitochondrial adaptations in C2C12 myotubes - Shih-Hua Fang; Ming-Ru Chiang; Chia-Yang Li; Pei-Ying Li; Zong-Jia Wu; Hsin-Hua Li (Journal of Muscle Research and Cell Motility, 2026)

Short-, medium-, and long-chain chlorinated paraffins in sediments from the Pearl River Delta, China: Occurrence, sources, and risks - Fei-Xiang Xie; Yu-Fang Huang; Yong-Hong Zhang; Ya-Hui Xue; Run-Lin Chen; Xiao-Mei Huang; Hong-De Shi; Jia-Hui Huang; Hui-Ru Li (Science of The Total Environment, 2026)

Lactic acid modulates empty-cup aroma persistence in Baijiu via molecular interaction mechanisms: a case study of strong-aroma and soy-sauce-aroma Baijiu - Qing-Ru Liu; Shun-Hua Zhang; Xiao-Juan Zhang; Zheng-Juan Zhu; Ru-Yi Li; Song-Tao Wang; Jin-Song Shi; Su-Yi Zhang; Cai-Hong Shen; Guan-Yu Fang; Qing-Qing Liu; Yong-Jun Yuan; et al. (Food Chemistry, 2026)

Biochar-based oxygen electrocatalysts for advanced Zn-air batteries: Mechanisms, applications, and prospects - Xiao-ru Meng; Shuai Gao; Janusz A. Kozinski; Roger Ruan; Zhen Fang (Chemical Engineering Journal, 2026)

Mechanisms and Scenario Predictions of the Digital Economy’s Impact on Pollution and Carbon Emission Reduction: A Case Study of the Yellow River Basin in China - Tianle Shi; Zhengmeng Hou; Jianhua Liu; Hao Fang; Qichen Wang; Yilin Guo; Ru Zhang; Liangchao Huang (International Journal of Environmental Research, 2026)
This study investigates how the digital economy reduces pollution and carbon emissions (RPCE) in the Yellow River Basin through three core mechanisms: (1) enabling real-time environmental monitoring and precision regulation, (2) fostering enterprise green production via digital transformation, and (3) driving technological innovation and industrial upgrading, proposing three testable hypotheses on these pathways. Indicators for the digital economy and RPCE are developed, and a spatiotemporal analysis of RPCE levels is conducted at both the municipal and grid scales. Employing the STIRPAT (Stochastic Impacts by Regression on Population, Affluence, and Technology) model to comprehensively examine population, affluence, and technology drivers, and innovatively integrating analysis at both municipal and grid scales to overcome traditional limitations, this study examines the direct and mediating effects of the digital economy on RPCE, along with heterogeneity analysis, endogeneity discussions, and exogenous shock tests, providing a more refined framework for revealing the mechanisms. Based on empirical findings, future RPCE trends in the basin are projected, with a proposed three-pronged strategy: digital infrastructure deployment, sector-specific interventions, and place-based prioritization (technology-upgrading midstream; clean-energy transition upstream). The main conclusions are as follows: (1) During the study period, RPCE in the Yellow River Basin showed significant improvement, with an upstream > downstream > midstream pattern and a block-like distribution. (2) The statistically significant regression coefficient (β = -0.476, p < 0.01) indicates a positive impact of the digital economy on RPCE, thus validating Hypothesis 1. Both technological innovation and industrial structure upgrading serve as positive mediators in the influence of the digital economy on RPCE, confirming Hypotheses 2 and Hypotheses 3. (3) The growth rate of population size is a major factor driving divergence in the RPCE index across the basin. To advance RPCE in the Yellow River Basin, policies should prioritize the development of the digital economy while promoting high-quality economic growth and stabilizing population growth rates.

Mechanistic link between eIF4E phosphorylation and viral pathogenesis: Therapeutic insights from a porcine model - Wen-Jun Tian; Yan-Ru Zhang; Jing-Ling You; Xiao-Jie Wu; Xiao-Fang Hu; Xiao-Jia Wang (Veterinary Microbiology, 2026)

Dual-dynamic polyimide and its thermally conductive adhesive featuring high glass transition temperature, recyclability, and strong adhesion - Fang Li; Ping Yu; Bin Wu; Ming Cao; Ru Xia; Jiasheng Qian (Chemical Engineering Journal, 2026)

Fermented Broussonetia papyrifera leaves on growth performance, immune responses, and resistance to Vibrio of shrimp - Guan-Lin Lai; Yu-Ru Lin; Ta-Jeng Yang; Yu-Ting Chu; Fan-Hua Nan; Yeh-Fang Hu (Fish & Shellfish Immunology, 2025)

Effects of feed supplementation with fermented Broussonetia papyrifera leaves on non-specific immune responses, resistance to Vibrio parahaemolyticus, growth, intestinal histology, and microbiota of white shrimp (Penaeus vannamei) - Guan-Lin Lai; Yu-Ru Lin; Ta-Jeng Yang; Yu-Ting Chu; Fan-Hua Nan; Yeh-Fang Hu (Fish & Shellfish Immunology, 2025)

Natural and built environments and heart failure risk: An exposome-wide analysis in the UK Biobank - Xuewei Huang; Siyu Yin; Meng Yao; Fang Lei; Weifang Liu; Lijin Lin; Tao Sun; Yuanyuan Cao; Xingyuan Zhang; Ru Li; Liwen Wang; Yufeng Hu; et al. (Environmental Research, 2025)

Selective energy transfer via chromium clusters for high-performance blue-excitable shortwave infrared phosphors - Shih-En Chen; Kuan-Chun Chen; Chuan-Fang Tsao; Yu-Chieh Huang; Agata Lazarowska; Mikołaj Kamiński; Natalia Majewska; Tadeusz Leśniewski; Grzegorz Leniec; Ewa Mijowska; Ding-Hwa Cherng; Ting-Wei Yeh; et al. (Chemical Engineering Journal, 2025)

Metagenome-assembled genomes reveal Pseudogracilibacillus amylolyticus sp. nov., a functional uncultured microorganism in high-temperature Daqu - Ai-Ping Lv; Ying-Han; Bao-Zhu Fang; Guo-Zheng Wang; Man-Chun Liu; Bing-Ru Bian; Zhuo-Huan Zheng; Kai Li; Bing-Yu Li; Jian-Yu Jiao; Lan Liu; Lei Dong; et al. (Systematic and Applied Microbiology, 2025)

A nonlocal strain gradient higher-order beam theory and its application to wave propagation in radially graded nanotubes - Wei-Li Ma; Peng-Yu Wang; Hui-Ru Cui; Xian-Fang Li (Ocean Engineering, 2025)

Inhibition of the NLR pathway alleviates MAPK1 mutation-driven proliferation and differentiation deficits and enhanced apoptosis in P19 cells - Tingying Lei; Lei Liu; Fei Guo; Ru Li; Li Zhen; Fang Fu; Min Pan; Jin Han; Hang Zhou; Chunling Ma; Ruibin Huang; Xinyi Zhao; et al. (Tissue and Cell, 2025)

Genetic burden and multidimensional predictors in prenatal diagnosis of fetal congenital diaphragmatic hernia - Ruibin Huang; Fang Fu; Shanshan Mei; Liyuan Liu; Wei Zhong; Jin Han; Qiuxia Yu; Hang Zhou; Chunling Ma; Li Zhen; Min Pan; Qiong Deng; et al. (Human Genetics, 2025)

First experiment using post-accelerated unstable ion beams at BRIF: angular distribution of the 21 , 22 Na elastic scattering from doubly magic 40 Ca - Wei Nan; Bing Guo; Cheng-Jian Lin; Dan-Yang Pang; Lei Yang; Dong-Xi Wang; Guo Yang; Yang-Ping Shen; Bing Tang; Qi-Wen Fan; Yi-Wen Bao; Lei Cao; et al. (Science Bulletin, 2025)

DEHP and its metabolite MEHP exposure impairs endometrial decidualization during early pregnancy via up-regulation of Mtmr6 - Li-Ping Tan; Liu Yuan; Yan Zhang; Jun-Lin He; Xin Yin; Yi-Dan Ma; Xue-Mei Chen; Wei-Ke Li; Fang-Fang Li; Ru-Fei Gao (Reproductive Toxicology, 2025)

Metabolic mechanisms of marine microalgae in response to selenite and selenate: Implications for selenium enrichment and environmental remediation - Ru Chen; Kuo Fang; YiMei Xi; FanTao Kong; XinJie Wang; WeiMing Li; XiangFeng Zeng; YongFeng Jia (Journal of Hazardous Materials, 2025)

Electrocatalytic synergistic degradation of tetracycline by low-energy-consumption Mn0.22-NiS nanosheet electrodes: Interface mechanism and toxicity analysis - Fan-Hao Hu; Qun-Feng Ye; Si-Ru Chen; Ya-Wen Yu; Hao Chen; Su-Fang Qin; Le-Xing You; Xiao-Chun Tian; Feng Zhao (Chemical Engineering Journal, 2025)

Orchard variable rate spraying method and experimental study based on multidimensional prescription maps - Chenming Hu; Yu Ru; Shuping Fang; Zifan Rong; Hongping Zhou; Xianghai Yan; Mengnan Liu (Computers and Electronics in Agriculture, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Greenhouse gas emissions and carbon sequestration capacity of constructed wetlands with different hydrophytes - Yajie Zhang; Xiaolu Zhang; Maoqing Wang; Ru Zhang; Yuehan Li; Guangming Zhang; Wei Fang; Panyue Zhang (Journal of Water Process Engineering, 2025)

Tracing anthropogenic imprints on polybrominated and polychlorinated dibenzo-p-dioxin/furans in soil: A comprehensive field study in an urban agglomeration of China - Ming-Yang Liu; Hui-Ru Li; Ping-An Peng; Ai-Min Song; Yang Li; Fei-Xiang Xie; Yong-Hong Zhang; Jian-Fang Hu (Environmental Research, 2025)

Integrative transcriptome and metabolome analyses provide insights into rice defence against Chilo suppressalis oviposition - Chen Shen; Haibo Bao; Zhengping Yu; Xiaoyan Cang; Ru Zhang; Junxian Song; Guanghua Luo; Jichao Fang (Plant Molecular Biology, 2025)

Unveiling a new hemocyte subpopulation in white shrimp (Penaeus vannamei) and the characterization of immune response in hemocyte subpopulation - Novi Rosmala Dewi; Ari Widodo; Muhammad Ar Rozzaaq Nugraha; Min-Da Yang; Ta-Jeng Yang; Yu-Ru Lin; Yeh-Fang Hu (Fish & Shellfish Immunology, 2025)

Fluorinated Amino-acid-doped microarray-based biochemical patches Deciphers in-situ spatiotemporal dynamics amidst intricate Bio-Interfaces - Ru Zhang; Ran Duan; Deqi Yang; Haofan Wu; Bingfang Wang; Zhiqiang Chang; Jing Chen; Jing Dai; Yingying Lv; Yi Liu; Menahem Y. Rotenberg; Dandan Liang; et al. (Chemical Engineering Journal, 2025)

Engineering an Ag2Se@PANi core–shell nanozymes – Klebsiella pasteurii hybrid system with enhanced ammonia synthesis - Meng-Xin Zhao; Si-Ru Chen; Bo Hu; Hao Chen; Ya-Xuan Xiao; Ting-Ting Liu; Shan-Shan Hu; Su-Fang Qin; Xuee Wu; Le-Xing You; Feng Zhao (Bioresource Technology, 2025)

Multi-scale characteristics and statistically associated factors of ozone pollution in Hangzhou based on machine learning - Yu-ting He; Tao Ding; Ru Yi; Yuan-yuan Wang; Yi Fu; Cheng-kai Tu; Hong-yan Fang; Jin-ye Li; Ming Zhang (Atmospheric Pollution Research, 2025)

Combined exposure to atrazine and phoxim exacerbated the alterations of enzyme activity and abnormal gene expression in earthworms (Eisenia fetida) - Jinzhan Li; Jingwen Wang; Fang Shu; Nan Huang; Ru Jia; Yanhua Wang (Environmental Toxicology and Pharmacology, 2025)

Optimizing boron oxide-support interactions for enhanced catalytic stability in propane oxidative dehydrogenation - Jinshu Tian; Kerou Hu; Ling Fang; Chi Wang; Ru Kong; Mingwu Tan; Lili Zhang; Zhongting Hu; Xiaonian Li; Yihan Zhu (Chemical Engineering Journal, 2025)

Functional analysis of Ophraella communa Lesage OcomOBP11 in recognition of Ambrosia artemisiifolia L. volatiles - Yang Yue; Chao Ma; Yan Zhang; Wei-hua Ma; Jing-jing Wang; Zhen-ya Tian; Guang-mei Chen; Ru-wen Li; Jin-hua Li; Jing-fang Yang; Zhong-shi Zhou (Pesticide Biochemistry and Physiology, 2025)

Enhancing color conversion of perovskite quantum dot-based micro-light-emitting diodes via electrochemical etching and flow chemistry system - Wen-Tse Huang; Yen-Huei Lin; Po-Yi Tu; Loan Thi Ngo; Wei-Cheng Chen; Kai-Ling Liang; Yen-Hsiang Fang; Chaochin Su; Ru-Shi Liu (Chemical Engineering Journal, 2025)

Targeted restoration of endothelial hypoxic response prevents angiogenic bone loss against liver fibrosis - Nan Zhang; Sheng-Feng Bai; Jia-Ning Liu; Xin Huang; Lu Liu; Yu-Ru Gao; Si-Qi Ying; Chen-Xi Zheng; Hao-Kun Xu; Ji Chen; Xiao Lei; Yu-Bo-Han Zhang; et al. (Chemical Engineering Journal, 2025)

Corrigendum: Deciphering the influence of dietary synbiotics in white shrimp gut and its effects in regulating immune signaling pathways - Sofia Priyadarsani Das; Zaenal Abidin; Huai-Ting Huang; Yu-Ru Lin; Chih-Yang Huang; Yu-Sheng Wu; Yeh-Fang Hu; Fan-Hua Nan (Frontiers in Marine Science, 2025)

Generation characteristics of polybrominated and polychlorinated dibenzo-p-dioxins/furans (PBDD/Fs and PCDD/Fs) under varying incineration conditions of municipal solid waste - Ming-Yang Liu; Ai-Min Song; Hui-Ru Li; Sheng-Tao Ma; Ren-Jie Shang; Yao Xiao; Ping-An Peng; Jian-Fang Hu (Environmental Pollution, 2025)

A review on the genus Melodinus: traditional uses, phytochemical diversity and pharmacological activities of indole alkaloids - Si-Fan Teng; Fang-Ru Li; Qi-Min Cui; Afsar Khan; Ting He; Xiao-Dong Luo; Ya-Ping Liu; Gui-Guang Cheng (Phytochemistry Reviews, 2025)

Performances and mechanisms of granular activated carbon enhancing n-caproate production via chain elongation - Ru Zhang; Wei Fang; Qingyan Wang; Ziyi Fang; Jinsong Liang; Le Chen; Jianning Chang; Yajie Zhang; Wenjing Yang; Panyue Zhang; Guangming Zhang (Journal of Environmental Management, 2025)

Efficient adsorption behavior of Fe-based ternary magnetic LDHs for naphthalene acetic acid: Role of Fe element - Ning Liu; Ti-Bo Fang; Ling-Xi Zhao; Na Li; Xiang-Feng Chen; Ru-Song Zhao (Environmental Research, 2025)

The impact of carbon emissions trading policy on green transformation of manufacturing industry: a test based on a time-varying DID model - Cong Hui Zhu; Mei Ling Wang; Hao Jie Gu; Yong Qi Fang; Hui Ru Chen (Clean Technologies and Environmental Policy, 2025)

The effects of water flow velocity and odor release frequency on the odor-tracking behavior of swimming crabs (Portunus trituberculatus) - Ru Wang; Xin Wang; Qihang Liang; Teng Jiang; Liang Yue; Fang Wang; Dapeng Liu (Aquaculture, 2025)

Depositional age and tectonic setting of the Dimunalike iron formation in southeast Tarim Craton: Implications for the resurgence of Neoproterozoic iron formations - Xiang Li; Ru-Xiong Lei; Matthew J. Brzozowski; Hui Ye; Xiu-Fang Wang; Zhi-Hua Zhang; Chang-Zhi Wu (Precambrian Research, 2025)

Effect of vacuum frying on the structure and bioactivity of proanthocyanidins in Chinese quince (Chaenomeles sinensis Koehne) fruit - Yu Lou; Xu Fang; Zi-Cheng Yang; Jia-Lin Fei; Yu-Ru Feng; Zhao Qin; Hua-Min Liu; Yu-Xiang Ma; Xue-De Wang (Food Chemistry, 2025)

Rapid and visual detection of the strawberries pathogenic fungi Fusarium oxysporum and Colletotrichum siamense by one-pot LAMP-CRISPR/Cas12b - Ya-Ru Tian; Dong-Lan Tang; Tian-Qi Wang; Jia-Yue Chen; Yan-Fang Dong; Xin-Yu Ying; Dan Zhang; Wen-Jing Wang; Zhi-Dan Luo (Journal of Plant Diseases and Protection, 2025)

Persistence evaluation of fecal pollution indicators in dewatered sludge and dewatering filtrate of municipal sewage sludge: The impacts of ambient temperature and conditioning treatments - Yuhang Wang; Hua Li; Wenhao Fang; Ru Wang; Xinxin Wang; Xiaomeng Wang; Guanyu Zheng; Lixiang Zhou (Water Research, 2025)

Leveraging Bio-Waste onion skin for High-Performance triboelectric nanogenerators - Po-Yen Chang; Ting-Ying Huang; Chien-Hung Yang; Chia-Hsien Lee; Ru-Jong Jeng; Chih-Ping Chen; Meng-Fang Lin (Chemical Engineering Journal, 2025)

Dynamic responses of the inter-microbial synergism and thermodynamic conditions attribute to the inhibition-and-relief effects of chitosan towards anaerobic digestion - Ru Fang; Xueting Wang; Zhibang Han; Ruirui Pang; Dong Wu; Jun Tai; Chuang Ouyang; Min Zhan; Hyunook Kim; Bing Xie; Yinglong Su (Water Research, 2024)

KLK7, KLK10, and KLK11 in Papillary Thyroid Cancer: Bioinformatic Analysis and Experimental Validation - Tao Ni; Ru-hua Zhao; Jing-fang Wu; Chao-you Li; Gang Xue; Xu Lin (Biochemical Genetics, 2024)

The different impacts of functional network centrality and connectivity on the complexity of brain signals in healthy control and first-episode drug-naïve patients with major depressive disorder - Shanling Ji; Wei An; Jing Zhang; Cong Zhou; Chao-Gan Yan; Xiao Chen; Li-Ping Cao; Wei Chen; Yu-Qi Cheng; Yi-Ru Fang; Qi-Yong Gong; Wen-Bin Guo; et al. (Brain Imaging and Behavior, 2024)

A novel strategy for waste activated sludge treatment: Recovery of structural extracellular polymeric substances and fermentative production of volatile fatty acids - Wei Fang; Ru Zhang; Wenjing Yang; Henri Spanjers; Panyue Zhang (Water Research, 2024)

Regulating N-doped biochar with Fe-Mo heterojunctions as cathode in long-life zinc-air battery - Xiao-ru Meng; Shuai Gao; Nianxi Liu; Pei-dong Wu; Zhen Fang (Chemical Engineering Journal, 2024)

Efficient recovery of all valuable metals from spent HDS catalysts: Based on roasting mechanisms for enhanced selective leaching and separation - Yixiong Chen; Xinsheng Wu; Wenjuan Guan; Shiyu Xiao; Kaiyuan Fang; Jialin Qing; Ru Xie; Shengxi Wu; Qinggang Li; Zuoying Cao; Mingyu Wang; Guiqing Zhang (Journal of Environmental Chemical Engineering, 2024)

Plantago asiatica seed as a protective agent for mitigating metals toxicity on Penaeus vannamei - Zhen-Hao Liao; Yeh-Fang Hu; Wen-Shao Wu; Huu-The Nguyen; Sofia Priyadarsani Das; Huai-Ting Huang; Yu-Ru Lin; Po-Tsang Lee; Fan-Hua Nan (Fish & Shellfish Immunology, 2024)

Mitigating thermal burden and enhancing minor phase emission energy transfer in perovskite by introducing dopamine-mediated silver nanoparticles - Zhen-Li Yan; Jhih-Yuan Chang; Chieh Tsao; Meng-Xiu Fang; Bi-Hsuan Lin; Jia-Hau Tsai; Mei-Hsin Chen; Ru-Jong Jeng; Chi-Ching Kuo (Chemical Engineering Journal, 2024)

Silencing of the Phytoene Desaturase (PDS) gene through virus infection using Tobacco Rattle Virus in Physalis grisea - Hai-Meng Zhang; Ru-Xin Wang; Yi-Ting Liu; Peng-Wei Jing; Qiao-Fang Shi; Yi-He Yu (Plant Cell, Tissue and Organ Culture (PCTOC), 2024)

Magnetic conjugated microporous polymer for rapid extraction and sensitive analysis of environmental endocrine disruptors in environmental waters and dairy products - Hai-Long Jiang; Fu-Shuai Kang; Ye-Fei Fan; Xia Wang; Yun-Liang Lin; Lu Liu; Wei Liu; Yan-Fang Zhao; Ru-Song Zhao (Analytica Chimica Acta, 2024)

Effects of melatonin on sperm quality, enzyme activity, antioxidant gene expression and fertility of cryopreserved bovine semen - Peng Niu; Fei Huang; Jie Wang; Jia-jia Suo; Jie-ru Wang; Di Fang; Chun-mei Han; Qing-hua Gao (Theriogenology, 2024)

The irregular developmental duration mainly caused by the broad-complex in Chilo suppressalis - Zhi-Ling Zhang; Qing-Yu Xu; Ru Zhang; Chen Shen; Hai-Bo Bao; Guang-Hua Luo; Ji-Chao Fang (Pesticide Biochemistry and Physiology, 2024)

Astrocyte Activation in the ACC Contributes to Comorbid Anxiety in Chronic Inflammatory Pain and Involves in The Excitation-Inhibition Imbalance - Naixuan Wei; Zi Guo; Mengting Qiu; Ru Ye; Xiaomei Shao; Yi Liang; Boyi Liu; Jianqiao Fang; Junfan Fang; Junying Du (Molecular Neurobiology, 2024)

Targeted liposomes for macrophages-mediated pulmonary fibrosis therapy - Yujie Wang; Fang Zhao; Xiangyu Wang; Haojie Zuo; Yiming Ru; Xi Cao; Yang Wang (Drug Delivery and Translational Research, 2024)

A comprehensive review of matcha: production, food application, potential health benefits, and gastrointestinal fate of main phenolics - Jian-Hui Ye; Qi-Ting Fang; Lin Zeng; Ru-Yi Liu; Lu Lu; Jun-Jie Dong; Jun-Feng Yin; Yue-Rong Liang; Yong-Quan Xu; Zhong-Hua Liu (Critical Reviews in Food Science and Nutrition, 2024)

Study on factors influencing carbon dioxide emissions and carbon peak heterogenous pathways in Chinese provinces - Runpu Liu; Yan Ru Fang; Shuan Peng; Nihed Benani; Xuefang Wu; Yushuo Chen; Tao Wang; Qimin Chai; Pingjian Yang (Journal of Environmental Management, 2024)

Effects of Taiwanese indigenous cinnamon (Cinnamomum osmophloeum) leaf hot-water extract on nonspecific immune responses, resistance against Vibrio parahaemolyticus, nonviable cells, and haemocyte subpopulations in white shrimp (Penaeus vannamei) - Muhammad Ar Rozzaaq Nugraha; Yu-Ru Lin; Novi Rosmala Dewi; Huai-Ting Huang; Fan-Hua Nan; Yeh-Fang Hu (Fish & Shellfish Immunology, 2024)

Rapid, sensitive, and visual detection of pseudorabies virus with an RPA-CRISPR/EsCas13d-based dual-readout portable platform - Dong You; Tong Xu; Bing-Zhou Huang; Fang Wu; Li-Shuang Deng; Zhe-Yan Liu; Liang-Peng Ge; Zuo-Hua Liu; Jing Sun; Xiu Zeng; Yuan-Cheng Zhou; Si-Yuan Lai; et al. (Analytica Chimica Acta, 2024)

Novel pyrrolidine-alkylamino-substituted dicyanoisophorone derivatives as near-infrared fluorescence probe for imaging β-amyloid in vitro and in vivo - Hui Zhou; Jihang Zhai; Huiyuan Gong; Ru Fang; Yongmei Zhao; Wen Luo (Analytica Chimica Acta, 2024)

C-Phycocyanin improves the quality of goat oocytes after in vitro maturation and vitrification - Xing-Yue Wang; Yang Gao; Hao-Ran Liu; Teng Wang; Meng-Lei Feng; Fang-Rui Xue; Kang Ding; Qi Yang; Zhao-Yu Jiang; Dui Sun; Chun-Ru Song; Xiao-Jie Zhang; et al. (Theriogenology, 2024)

Exploring efficient copper recovery and recycling in Taiwan's printed circuit board manufacturing through material-flow cost accounting - Fang-Ru Chou; Remi Chauvy; Pi-Cheng Chen (Sustainable Production and Consumption, 2024)

Enhancing propionic acid production in the anaerobic fermentation of high-strength starch wastewater facilitated by hydraulic retention time and FeCl3 under alkaline pH - Wenjing Yang; Wei Fang; Jianning Chang; Ru Zhang; Yajie Zhang; Maoqing Wang; Panyue Zhang (Journal of Water Process Engineering, 2024)

Path tracking control for brake-steering tracked vehicles based on an improved pure pursuit algorithm - Chenming Hu; Yu Ru; Xianzhe Li; Shuping Fang; Hongping Zhou; Xianghai Yan; Mengnan Liu; Rong Xie (Biosystems Engineering, 2024)

Enteral nutrition in the management of acute pancreatitis: Modulates gut microbiome and alleviates inflammation - Fang-Yuan Yang; Yi-Jing Cai; Xiao-Ying Niu; Shun-Fu Wang; Yu-Qi Wang; Sabola Eluby Esmie; Rui-Cong Chen; Sheng-Jie Dai; Hong-Ru Kong; Hong-Wei Sun; Ke-Qing Shi (Food Bioscience, 2024)

Halogenated aromatic pollutants in routine animal-derived food of south China: Occurrence, sources, and dietary intake risks - Li-Na Zhang; Ping-An Peng; Hui-Ru Li; Ming-Yang Liu; Jian-Fang Hu (Environmental Pollution, 2024)

A freestanding rotating triboelectric nanogenerator with large area and high efficiency for triboelectric plasma CO2 reduction - Hongjie Cao; Qinglong Ru; Dongyang Fang; Sumin Li; Nannan Liu; Wei Jiang; Hui Hu; Yongcui Yang; Guangqin Gu; Bao Zhang; Gang Cheng; Sanjun Yang; et al. (Chemical Engineering Journal, 2024)

Regulatory effect of Yinchenhao decoction on bile acid metabolism to improve the inflammatory microenvironment of hepatocellular carcinoma in mice - Jian Shi; Lin Zhu; Bang-Yi Tang; Wan-Qing Yang; Sheng-Yan Xi; Chen-Long Zhang; Peng-Fei Li; Yu-Jie Wang; Kai-Hang Guo; Jing-Ru Huang; Chen-Rui Huang; Zhou-Xin Yu; et al. (Journal of Natural Medicines, 2024)

Initiation and Propagation of Interface Cracks in Layered Composite Rocks: An Investigation Using True Triaxial Experiments - Jian-Zhi Zhang; Tian-Tian Gu; Ru-Fang Zhan; Zhao-Peng Zhang (Geotechnical and Geological Engineering, 2024)

Dissolved oxygen and ammonia affect ammonia production via GDH/AMPK signaling pathway and alter flesh quality in Chinese perch (Siniperca chuatsi) - Ru Yang; Xuange Liu; Yong Liu; Qingda Tian; Ziwei Wang; Dejie Zhu; Zhisong Qian; Yi Yi; Jiacheng Hu; Yan Li; Xu-Fang Liang; Liwei Liu; et al. (Fish Physiology and Biochemistry, 2024)

Addition of α-ketoglutaric acid (AKG) reduces deamination in Chinese perch (Siniperca chuatsi) fed with fermented soybean meal as a substitute for fishmeal - Yufei Zhang; Jiacheng Hu; Peisong Lu; Ru Yang; Xu-Fang Liang; Liwei Liu (Fish Physiology and Biochemistry, 2024)

Molecular epidemiological and clinical infection characteristics analysis of Ralstonia - Zhaojun Sheng; Jiaxin Li; Guojing Han; Ru Fan; Pingjun Zhu; Xiangqun Fang (European Journal of Clinical Microbiology & Infectious Diseases, 2024)
Purpose This study was to clarify the molecular epidemiology and clinical infection characteristics of Ralstonia pickettii and establish sequence typing system. Methods 48 nonrepetitive Ralstonia pickettii strains were collected from January 2008 to December 2013 at the Chinese People’s Liberation Army General Hospital (PLAGH) and were identified through a specific PCR experiment, 16 S rDNA experiment and VITEK 2 system to compare the identification accuracy. The sequence types of the strains were analyzed by multilocus sequence typing (MLST) method. The antibiotic sensitivity of these strains was determined with disc diffusion tests and broth microdilution method. The clinical data of Ralstonia pickettii infected patients were collected. Results All of the 48 strains were identified as Ralstonia pickettii by VITEK 2 system. 30 and 34 strains were identified as Ralstonia pickettii by PCR and 16 S rDNA experiment respectively. ST9 was the most sequence types (STs) in these 18 STs of 42 strains. 42 strains were divided into 2 groups (A and B) and 18 genotypes. Ralstonia pickettii was sensitive to some cephalosporins, β-lactam/β-lactamase inhibitor, levofloxacin and trimethoprim/sulfamethoxazole. Cough, sputum, shortness of breath and pulmonary rales were the common clinical symptoms of most Ralstonia pickettii infected patients. Conclusion We established a sequence typing system with a relatively fine resolution and the PCR assay is a faster and more sensitive method for clinical identification of Ralstonia pickettii . ST9 is the most common sequence types of Ralstonia pickettii . The most common clinical characteristics of Ralstonia pickettii infected patients were cough, sputum, shortness of breath and pulmonary rales.

Assessing climate/air quality synergies and cost-effectiveness for Beijing transportation: Insights into sustainable development - Xuefang Wu; Roy M. Harrison; Min Chen; Tao Wang; Ruihe Lyu; Shuan Peng; Runpu Liu; Yushuo Chen; Yan Ru Fang; Pingjian Yang (Sustainable Cities and Society, 2024)

Insights into the influence of polystyrene microplastics on the bio-degradation behavior of tetrabromobisphenol A in soil - Jianning Chang; Jinsong Liang; Yajie Zhang; Ru Zhang; Wei Fang; Haibo Zhang; Su Shiung Lam; Panyue Zhang; Guangming Zhang (Journal of Hazardous Materials, 2024)

Effect of ultrasound-assisted enzyme pretreatment on γ-aminobutyric acid content, eating quality and starch properties of germinated brown rice - Bing-jie Chen; Xiao Wang; Hong-ru Liu; Yi Zhang; Song-heng Wu; Chun-fang Wang; Chen-xia Liu; Yong-jin Qiao (Journal of Cereal Science, 2024)

Anhydride esterification to regulate water migration and reduce ice crystal formation in κ-carrageenan gel during freezing - Xinwei Xu; Feng Jiang; Kuncheng Lin; Jingjing Fang; Fuquan Chen; Yi Ru; Huifen Weng; Qiong Xiao; Qiuming Yang; Anfeng Xiao (Food Hydrocolloids, 2024)

Arabidopsis HAPLESS13/AP-1µ is critical for pollen sac formation and tapetal function - Gui-Min Yin; Yi-Ru Fang; Jia-Gang Wang; Yue Liu; Xiaojiao Xiang; Sha Li; Yan Zhang (Plant Science, 2024)

Fabrication of hyaluronic acid-altered gold complex delivery for head and neck squamous cell carcinoma therapy with high antitumor efficacy and low in vivo toxicity - Shizhi He; Jiaming Chen; Yanming Zhao; Ru Wang; Yurong He; Shaoshi Chen; Yifan Yang; Changyu Zhu; Jingyang Zhao; Jugao Fang (Journal of Photochemistry and Photobiology B: Biology, 2024)

Experimental study of the influence factors of the droplet size of rotary nozzles during manned helicopter spraying operations - Yu Ru; Shuping Fang; Jiangkun Xue; Chenming Hu; Jie Zhou (Crop Protection, 2024)

Lower-bound shakedown solutions for transportation infrastructures subjected to moving harmonic loads: A focus on saturated subgrade support - Yuanxiang Lin; Jun-Jie Zheng; Hao Fang; Ru-Yi Hou; Yifan Guo (Transportation Geotechnics, 2024)

Tyrosine hydroxylase plays crucial roles in larval cuticle formation and larval-pupal tanning in the rice stem borer, Chilo suppressalis - Qing-Yu Xu; Zhi-Ling Zhang; Ru Zhang; Ary A. Hoffman; Ji-Chao Fang; Guang-Hua Luo (Pesticide Biochemistry and Physiology, 2024)

Facile synthesis of hydroxylated triazine-based magnetic microporous organic network for ultrahigh adsorption of phenylurea herbicides: An experimental and density-functional theory study - Lu Liu; Lu-Qin Qiao; Feng Liu; Qian-Yun Sun; Yan-Fang Zhao; Xiao-Li Wang; Na Li; Hai-Long Jiang; Xiang-Feng Chen; Ming-Lin Wang; Yong-Ning Wu; Ru-Song Zhao (Journal of Hazardous Materials, 2024)

6PPD-quinone exposure induces neuronal mitochondrial dysfunction to exacerbate Lewy neurites formation induced by α-synuclein preformed fibrils seeding - Jiacheng Fang; Xiaoxiao Wang; Guodong Cao; Fuyue Wang; Yi Ru; Bolun Wang; Yanhao Zhang; Doudou Zhang; Jie Yan; Ji Xu; Jing Ji; Fenfen Ji; et al. (Journal of Hazardous Materials, 2024)

Design of a tulobuterol patch with improved mechanical properties: effect of transdermal permeation enhancers on the release process of metal ligand-based acrylic pressure-sensitive adhesives - Longyi Nan; Haoyuan Song; Haijun Wang; Ru Mi; Xiaoxu Wang; Liang Fang (Drug Delivery and Translational Research, 2024)

Deciphering the influence of dietary synbiotics in white shrimp gut and its effects in regulating immune signaling pathways - Sofia Priyadarsani Das; Zaenal Abidin; Huai-Ting Huang; Yu-Ru Lin; Chih-Yang Huang; Yu-Sheng Wu; Yeh-Fang Hu; Fan-Hua Nan (Frontiers in Marine Science, 2024)
The health of the host is significantly influenced by the gut microbiota. Penaeus vannamei (white shrimp) is one of the most profitable aquaculture species globally. Synbiotics are typically used as a beneficial diet supplement for raising aquaculture species’ growth capacities and enhancing immunity against pathogenicity. However, the effects of synbiotics on the white shrimp intestinal microbiota remain poorly understood. In the present study, we targeted the V3–V4 region of 16S rRNA genes to analyze the effects of synbiotics on white shrimp gut microbiota. Dietary synbiotics, having Lactobacillus acidophilus , and Moringa oleifera leaf extract were added to the white shrimps’ feed in various proportions in the present study. In total, 490 operational taxonomic units yielding 23 phyla, 41 classes, 94 orders, 151 families, and 250 genera of microorganisms were obtained. The diet containing L. acidophilus at 1 × 10 7 CFU/g and M. oleifera at 2.5 g/kg led to an increase in the relative abundance of beneficial microorganisms through a significant decrease in the α diversity. Moreover, it upregulated several physiological pathways such as carbohydrate metabolism, signal transduction, lipid metabolism, nucleotide metabolism, amino acid metabolism, and environmental adaptation, which led to the upregulation of the AMPK, MAPK, P13K-Akt, lysosome, peroxisome, and ferroptosis signaling pathways; this enhanced growth and immunity in white shrimp. Whether a single species or a combination of different microorganisms improves growth and immunity remains unclear till now. Nevertheless, our results will facilitate further in-depth investigation into beneficial microbial communities for upliftment of white shrimp aquaculture.

Nitrite acts as the key “switch” governing the free nitrous acid pretreatment in anaerobic digestion: A comprehensive mechanism of abiotic, bioinformatics and bioenergetics effects - Zhibang Han; Ru Fang; Xueting Wang; Guangchen Huang; Dong Wu; Jun Tai; Bing Xie; Yinglong Su; Jingyang Luo; Gang Zhao; Ming Jiang (Chemical Engineering Journal, 2024)

Eco-friendly approach for enhancing the floatability of non-metallic components in waste printed circuit boards: Adding gutter oil during dry grinding - Chun-chen Nie; Si-qi Jiang; Xi-guang Li; Xiao-ru Wang; Zhi-hao Li; Xiang-nan Zhu; Xian-jun Lyu; Xiao-fang You; Lin Li (Waste Management, 2023)

Dietary soybean lecithin promoted growth performance and feeding in juvenile Chinese perch (Siniperca chuatsi) could be by optimizing glucolipid metabolism - Dongliang Wu; Di Peng; Xu-Fang Liang; Ruipeng Xie; Ming Zeng; Junliang Chen; Jie Lan; Ru Yang; Jiacheng Hu; Peisong Lu (Fish Physiology and Biochemistry, 2023)

Can Antibiotic Resistance Genes in Household Food Waste be Reduced by Earthworm Vermicomposting? Underpinning Mechanisms and Strategies - Ru Fang; Xiaojing Liu; Zhipeng Zheng; Baoyi Lv; Jie Wang; Yinglong Su; Bing Xie; Dong Wu (Reviews of Environmental Contamination and Toxicology, 2023)

Antioxidant CeO2 doped with carbon dots enhance ammonia production by an electroactive Azospirillum humicireducens SgZ-5T - Gao-Kai Wu; Meng-Xin Zhao; Si-Ru Chen; Yi-Nan Sun; Su-Fang Qin; Ai-Jun Wang; Qun-Feng Ye; Hend Alwathnani; Le-Xing You; Christopher Rensing (Chemosphere, 2023)

Recent advances in the unlined cast iron pipe scale characteristics, cleaning techniques and harmless disposal methods: An overview - Ming Li; Dong Zhang; Ru Zhang; Fang Wang; Yang Song; Feiyong Chen; Juan Yang; Changming Li (Chemosphere, 2023)

Mineralogy, petrology and P-T conditions of the spodumene pegmatites and surrounding meta-sediments in Lhozhag, eastern Himalaya - Jia-Min Wang; Kang-Shi Hou; Lei Yang; Xiao-Chi Liu; Ru-Cheng Wang; Guang-Ming Li; Jian-Gang Fu; Fang-Yang Hu; Yu-Lu Tian; Fu-Yuan Wu (Lithos, 2023)

Prenatal and postnatal exposure to heavy metals in PM2.5 and autism spectrum disorder - Hao-Hsuan Lin; Chau-Ren Jung; Chuan-Yao Lin; Ya-Chu Chang; Chia-Yun Hsieh; Pei-Chuan Hsu; Bao-Ru Chuang; Bing-Fang Hwang (Environmental Research, 2023)

Internal driving mechanisms of microbial community and metabolism for granular activated carbon enhancing anaerobic digestion of high-strength sulfate organic wastewater - Le Chen; Ru Zhang; Yuehan Li; Yajie Zhang; Wei Fang; Panyue Zhang; Guangming Zhang (Chemical Engineering Journal, 2023)

Mitogenome analysis reveals predominantly ancient Yellow River origin of population inhabiting Datong agro-pastoral ecotone along Great Wall - Yuqing Yan; Panxin Du; Jihong Zhang; Ruilan Li; Haoquan Bao; Qingli Fang; Ye Gao; Hailiang Meng; Yiran Xu; Haochen Shi; Hailong Yan; Xin Chang; et al. (Molecular Genetics and Genomics, 2023)

From air to airway: Dynamics and risk of inhalable bacteria in municipal solid waste treatment systems - Ru Fang; Tian Chen; Zhibang Han; Wenhui Ji; Yudan Bai; Zhipeng Zheng; Yinglong Su; Ling Jin; Bing Xie; Dong Wu (Journal of Hazardous Materials, 2023)

Adsorption behaviors and bioavailability of tetrabromobisphenol A in the presence of polystyrene microplastic in soil: Effect of microplastics aging - Jianning Chang; Jinsong Liang; Wei Fang; Haibo Zhang; Yajie Zhang; Hongjun Zhao; Ru Zhang; Panyue Zhang; Guangming Zhang (Environmental Pollution, 2023)

Highly effective and selective recovery of Gd(III) from wastewater by defective MOFs-based ion-imprinted polymer: Performance and mechanism - Ming yang; Yuxin Zhou; Dandan Zhang; Fang Zhou; Hui Ning; Maoxia He; Ru-an Chi; Weiyan Yin (Chemical Engineering Journal, 2023)

Metagenomic analysis reveals the efficient digestion mechanism of corn stover in Angus bull rumen: Microbial community succession, CAZyme composition and functional gene expression - Jinsong Liang; Jianning Chang; Ru Zhang; Wei Fang; Le Chen; Weifang Ma; Yajie Zhang; Wenjing Yang; Yuehan Li; Panyue Zhang; Guangming Zhang (Chemosphere, 2023)

A life-threatening bleeding prediction model for immune thrombocytopenia based on personalized machine learning: a nationwide prospective cohort study - Zhuo-Yu An; Ye-Jun Wu; Yu Hou; Heng Mei; Wei-Xia Nong; Wen-Qian Li; Hu Zhou; Ru Feng; Jian-Ping Shen; Jun Peng; Hai Zhou; Yi Liu; et al. (Science Bulletin, 2023)

Multi-material 3D printing of piezoelectric and triboelectric integrated nanogenerators with voxel structure - Fang Chen; Zimo An; Yinghong Chen; Yijun Li; Xingang Liu; Ning Chen; Yue Ru; Dali Gao (Chemical Engineering Journal, 2023)

Age- and gender-related dispersion of brain networks across the lifespan - Qing Wang; Lingyu Qi; Cancan He; Haixia Feng; Chunming Xie; Chao-Gan Yan; Xiao Chen; Le Li; Francisco Xavier Castellanos; Tong-Jian Bai; Ning-Xuan Chen; Wei Chen; et al. (GeroScience, 2023)

Carbonate-silicate interaction in subducting slabs recorded by Zn isotopes in western Alps metasediments - Yuan-Ru Qu; Sheng-Ao Liu; Vincent Busigny; Ze-Zhou Wang; Fang-Zhen Teng (Earth and Planetary Science Letters, 2023)

Xanthine-derived reactive oxygen species exacerbates adipose tissue disorders in male db/db mice induced by real-ambient PM2.5 exposure - Leijian Chen; Huankai Li; Yi Ru; Yuanyuan Song; Yuting Shen; Lifang Zhao; Gefei Huang; Yi Chen; Zenghua Qi; Ruijin Li; Chuan Dong; Jiacheng Fang; et al. (Science of The Total Environment, 2023)

Associations of long-term joint exposure to various ambient air pollutants with all-cause and cause-specific mortality: evidence from a large population-based cohort study - Zhi-Hao Li; Xiao-Meng Wang; Jia-Xuan Xiang; Ying Nan; Ying-Jun Chen; Pei-Dong Zhang; Dan Liu; Dong Shen; Xi-Ru Zhang; Wen-Fang Zhong; Pei-Liang Chen; Qing-Mei Huang; et al. (Environmental Science and Pollution Research, 2023)

Planning the temporary takeoff/landing site’s location for a pesticide spraying helicopter based on an intelligent fusion algorithm - Shuping Fang; Yu Ru; Chenming Hu; Fengbo Yang; Jiangkun Xue; Jie Zhou (Computers and Electronics in Agriculture, 2023)

Volatile fatty acid production in anaerobic fermentation of food waste saccharified residue: Effect of substrate concentration - Qingyan Wang; Guangming Zhang; Le Chen; Nan Yang; Yan Wu; Wei Fang; Ru Zhang; Xinyi Wang; Chuan Fu; Panyue Zhang (Waste Management, 2023)

Ndufa4 Regulates the Proliferation and Apoptosis of Neurons via miR-145a-5p/Homer1/Ccnd2 - Fang Fu; Chen Chen; Kun Du; Lu-shan Li; Ru Li; Ting-ying Lei; Qiong Deng; Dan Wang; Qiu-xia Yu; Xin Yang; Jin Han; Min Pan; et al. (Molecular Neurobiology, 2023)
The Dandy–Walker malformation (DWM) is characterized by neuron dysregulation in embryonic development; however, the regulatory mechanisms associated with it are unclear. This study aimed to investigate the role of NADH dehydrogenase 1 alpha subcomplex 4 (NDUFA4) in regulating downstream signaling cascades and neuronal proliferation and apoptosis. Ndufa4 overexpression promoted the proliferation of neurons and inhibited their apoptosis in vitro, which underwent reverse regulation by the Ndufa4 short hairpin RNAs. Ndufa4 -knockout (KO) mice showed abnormal histological alterations in the brain tissue, in addition to impaired spatial learning capacity and exploratory activity. Ndufa4 depletion altered the microRNA expressional profiles of the cerebellum: Ndufa4 inhibited miR-145a-5p expression both in the cerebellum and neurons. miR-145a-5p inhibited the proliferation of neurons and promoted their apoptosis. Ndufa4 promoted and miR-145a-5p inhibited the expression of human homer protein homolog 1 and cyclin D2 in neurons. Thus, Ndufa4 promotes the proliferation of neurons and inhibits their apoptosis by inhibiting miR-145a-5p, which directly targets and inhibits the untranslated regions of Homer1 and Ccnd2 expression.

Prenatal diagnosis in the fetal hyperechogenic kidneys: assessment using chromosomal microarray analysis and exome sequencing - Ruibin Huang; Fang Fu; Hang Zhou; Lu Zhang; Tingying Lei; Ken Cheng; Shujuan Yan; Fei Guo; You Wang; Chunling Ma; Ru Li; Qiuxia Yu; et al. (Human Genetics, 2023)

Valorization of soybean pulp for sustainable α-ketoisocaproate production using engineered Bacillus subtilis whole-cell biocatalyst - Eugene Huang; Jhen-Sheng Yan; Ronnie G. Gicana; Yin-Ru Chiang; Fang-I Yeh; Chieh-Chen Huang; Po-Hsiang Wang (Chemosphere, 2023)

Planning of takeoff/landing site location, dispatch route, and spraying route for a pesticide application helicopter - Fang Shuping; Ru Yu; Hu Chenming; Yang Fengbo (European Journal of Agronomy, 2023)

mRNA 3ʹ -UTR-mediate translational control through PAS and CPE in sheep oocyte - Chun-Ru Song; Ru-Jing Zhang; Fang-Rui Xue; Xiao-Jie Zhang; Xing-Yue Wang; Dui Sun; Kang Ding; Qi Yang; Xin-Yu Wang; Cheng-Guang Liang (Theriogenology, 2023)

Magnetic ternary layered double hydroxides for efficient removal of 1-naphthalene acetic acid from waters: Adsorption behavior and mechanism - Ti-Bo Fang; Hua Xiao; Ling-Xi Zhao; Na Li; Ling-Yu Luan; Zhao-Xing Yan; Jin-Ming Lin; Ru-Song Zhao (Journal of Environmental Chemical Engineering, 2023)

Toward sustainable utilization of crop straw: Greenhouse gas emissions and their reduction potential from 1950 to 2021 in China - Wenjun Shi; Yan Ru Fang; Yuyang Chang; Guang Hui Xie (Resources, Conservation and Recycling, 2023)

Whole exome sequencing improves genetic diagnosis of fetal clubfoot - Ruibin Huang; Hang Zhou; Chunling Ma; Fang Fu; Ken Cheng; You Wang; Ru Li; Tingying Lei; Qiuxia Yu; Dan Wang; Shujuan Yan; Xin Yang; et al. (Human Genetics, 2023)

The preparation of Co/γ-Al2O3 and treatment of cartap pesticide wastewater by microwave catalytic oxidation - Jia Ru Dai; Kai Xuan Liu; Fang Lian; Xue Peng Tian; Yu Feng Zhang (Journal of Water Process Engineering, 2023)

Effects of polystyrene nanoplastics on the physiological and biochemical characteristics of microalga Scenedesmus quadricauda - Ru-ru Li; Bin-liang Wang; Fang-ru Nan; Jun-ping Lv; Xu-dong Liu; Qi Liu; Jia Feng; Shu-lian Xie (Environmental Pollution, 2023)

Viewing landfill-borne antibiotic resistance genes through the kaleidoscope of “One Health”: Essential legacies and research needs from the environmental dimension - Dong Wu; Ru Fang; Bing Xie (Current Opinion in Environmental Science & Health, 2023)

Narrowing fossil fuel consumption in the Indian road transport sector towards reaching carbon neutrality - M.S. Hossain; Yan Ru Fang; Teng Ma; Chen Huang; Wei Peng; Johannes Urpelainen; Chetan Hebbale; Hancheng Dai (Energy Policy, 2023)

Two new aromatic derivatives from Codonopsis pilosula and their α-glucosidase inhibitory activities - Ru-Yue Wang; Pan-Jie Su; Bing Li; Xiao-Qing Zhan; Feng-Ming Qi; Chun-Wei Lv; Fang-Di Hu; Kun Gao; Zhan-Xin Zhang; Dong-Qing Fei (Natural Product Research, 2022)

Deciphering the Heterogeneity of Mitochondrial Functions During Hematopoietic Lineage Differentiation - Haoyue Liang; Shuxu Dong; Weichao Fu; Sen Zhang; Wenying Yu; Fang Dong; Baolin He; Jinhong Wang; Yingdai Gao; Yuan Zhou; Yongxin Ru (Stem Cell Reviews and Reports, 2022)

miR-211-3p enhances induction chemotherapy insensitivity by upregulating CSF2/CCL20/TNF signaling in hypopharyngeal squamous cell carcinoma - Lingwa Wang; Ru Wang; Tianqiao Huang; Yifan Yang; Ling Feng; Jugao Fang (Molecular Biology Reports, 2022)

Imatinib-induced hepatotoxicity via oxidative stress and activation of NLRP3 inflammasome: an in vitro and in vivo study - Feng-Ru Huang; Wen-Tong Fang; Zi-Ping Cheng; Ye Shen; Dun-Jian Wang; Yong-Qing Wang; Lu-Ning Sun (Archives of Toxicology, 2022)

Synthesis and biological activity of amide derivatives derived from natural product Waltherione F - Hongbin Fang; Zhanfang Chen; Xuewen Hua; Wenrui Liu; Chenmeng Xue; Yi Liu; Xiaohe Zhu; Man Yuan; Shuang Cheng; Bingxiang Wang; Jing Ru; Dzmitry Bazhanau; et al. (Medicinal Chemistry Research, 2022)

Identification and antimicrobial properties of a new alkaloid produced by marine-derived Verrucosispora sp. FIM06-0036 - Ming-Hong Chen; Yun-Yang Lian; Dong-Sheng Fang; Li Chen; Jia Jia; Wen-Long Zhang; Ru Lin; Yang Xie; Hong-Kai Bi; Hong Jiang (Natural Product Research, 2021)

Interactive effects of nutrient availability, fluctuating supply, and plant parasitism on the post-invasion success of Bidens pilosa - Fang-Lei Gao; Qiao-Sheng He; Ru-Qian Xie; Jia-Hui Hou; Chen-Lu Shi; Jun-Min Li; Fei-Hai Yu (Biological Invasions, 2021)

Genetic Analysis of ZNF Protein Family Members for Early-Onset Parkinson’s Disease in Chinese Population - Chun Yu Li; Ru Wei Ou; Yong Ping Chen; Xiao Jing Gu; Qian Qian Wei; Bei Cao; Ling Yu Zhang; Yan Bing Hou; Kun Cheng Liu; Xue Ping Chen; Wei Song; Bi Zhao; et al. (Molecular Neurobiology, 2021)

Anthropogenic Sound Exposure-Induced Stress in Captive Dolphins and Implications for Cetacean Health - Wei-Cheng Yang; Chi-Fang Chen; Yee-Chien Chuah; Chun-Ru Zhuang; I-Hua Chen; T. Aran Mooney; Jeff Stott; Myra Blanchard; I-Fan Jen; Lien-Siang Chou (Frontiers in Marine Science, 2021)
Many cetaceans are exposed to increasing pressure caused by anthropogenic activities in their marine environment. Anthropogenic sound has been recognized as a possible stressor for cetaceans that may have impacts on health. However, the relationship between stress, hormones, and cytokines secretion in cetaceans is complex and not fully understood. Moreover, the effects of stress are often inconsistent because the character, intensity, and duration of the stressors are variable. For a better understanding of how anthropogenic sounds affect the psychophysiology of cetaceans, the present study compared the changes of cortisol concentration and cytokine gene transcriptions in blood samples and behaviors of captive bottlenose dolphins ( Tursiops truncatus ) after sound exposures. The sound stimuli were 800 Hz pure-tone multiple impulsive sound for 30 min at three different sound levels (estimated mean received SPL: 0, 120, and 140 dB re 1 μPa) that likely cause no permanent and temporary hearing threshold shift in dolphins. Six cytokine genes (IL-2Rα, IL-4, IL-10, IL-12, TNF-α, and IFN-γ) were selected for analysis. Cortisol levels and IL-10 gene transcription increased and IFNγ/IL-10 ratio was lower after a 30-min high-level sound exposure, indicating the sound stimuli used in this study could be a stressor for cetaceans, although only minor behavior changes were observed. This study may shed light on the potential impact of pile driving-like sounds on the endocrine and immune systems in cetaceans and provide imperative information regarding sound exposure for free-ranging cetaceans.

Genetic Analysis of Prosaposin, the Lysosomal Storage Disorder Gene in Parkinson’s Disease - Yong-Ping Chen; Xiao-Jing Gu; Ru-Wei Ou; Ling-Yu Zhang; Yan-Bing Hou; Kun-Cheng Liu; Bei Cao; Qian-Qian Wei; Wei Song; Bi Zhao; Ying Wu; Jing-Qiu Cheng; et al. (Molecular Neurobiology, 2021)

Alkaloids and phenylpropanoid from Rhizomes of Arundo donax L - Qing-Ru Liu; Juan Li; Xiao-Fang Zhao; Bo Xu; Xing-Hua Xiao; Jie Ren; Shun-Xiang Li (Natural Product Research, 2021)

Compound heterozygous mutation of the ASXL3 gene causes autosomal recessive congenital heart disease - Fang Fu; Ru Li; Ting-ying Lei; Dan Wang; Xin Yang; Jin Han; Min Pan; Li Zhen; Jian Li; Fa-tao Li; Xiang-yi Jing; Dong-zhi Li; et al. (Human Genetics, 2021)

FW0622, a new siderophore isolated from marine Verrucosispora sp. by genomic mining - Wei Zhao; Fei Peng; Chuan-xi Wang; Yang Xie; Ru Lin; Zhi-kai Fang; Fei Sun; Yun-yang Lian; Hong Jiang (Natural Product Research, 2020)

Corticosterone Induced the Increase of proBDNF in Primary Hippocampal Neurons Via Endoplasmic Reticulum Stress - Yu Liu; Guang-Jing Zou; Bo-Xuan Tu; Zhao-Lan Hu; Cong Luo; Yan-Hui Cui; Yang Xu; Fang Li; Ru-Ping Dai; Fang-Fang Bi; Chang-Qi Li (Neurotoxicity Research, 2020)

Prenatal di-(2-ethylhexyl) phthalate maternal exposure impairs the spatial memory of adult mouse offspring in a phase- and gender-dependent manner - Ling-Li Zhao; Ru Shen; Cong-Cong Sun; Shan-Yu Zhang; Bo Wang; Mei-Fang Sun; De-Xiang Xu (Environmental Science and Pollution Research, 2020)

Correction to: Micropropagation of tree peony (Paeonia sect. Moutan): A review - Shu-Sheng Wen; Lan Chen; Fang-Yun Cheng; Ru-Nan Tian (Plant Cell, Tissue and Organ Culture (PCTOC), 2020)

The effective use of camera traps to document the northernmost distribution of the western black crested gibbon in China - Yi-Hao Fang; Yan-Peng Li; Guo-Peng Ren; Zhi-Pang Huang; Liang-Wei Cui; Li-Xiang zhang; Paul A. Garber; Ru-Liang Pan; Wen Xiao (Primates, 2020)

Comprehensive transcriptome analysis of faba bean in response to vernalization - Bei Gao; Xiao-Chun Bian; Feng Yang; Mo-Xian Chen; Debatosh Das; Xiu-Ru Zhu; Yong Jiang; Jianhua Zhang; Yun-Ying Cao; Chun-Fang Wu (Planta, 2020)

Isolation, purification and identification of two new alkaloids metabolites from marine-derived Verrucosispora sp. FIM06025 - Ming-Hong Chen; Wen-Long Zhang; Li Chen; Ru Lin; Yang Xie; Dong-Sheng Fang; Yun-Yang Lian; Hong Jiang (Natural Product Research, 2019)

Cloning and characterization of terpene synthase genes from Taiwan cherry - Kuan-Feng Huang; Chi-Hsiang Wen; Yi-Ru Lee; Fang-Hua Chu (Tree Genetics & Genomes, 2019)

Heterologous overexpression of Lithospermum erythrorhizon LeERF-1 gene increases drought and pathogen resistance in Arabidopsis - Rong-Jun Fang; Ai-Qian Li; Ru-Nan Tian; Wen-Ju Zhang; Ai-Lan Zou; Feng-Yao Wu; Yong-Hui Liao; Xiao-Ming Wang; Yan-Jun Pang; Rong-Wu Yang; Gui-Hua Lu; Jin-Liang Qi; et al. (Acta Physiologiae Plantarum, 2019)

Structure elucidation and antitumour activity of a new macrolactam produced by marine-derived actinomycete Micromonospora sp. FIM05328 - Yi-Lei Nie; Yun-Dan Wu; Chuan-Xi Wang; Ru Lin; Yang Xie; Dong-Sheng Fang; Hong Jiang; Yun-Yang Lian (Natural Product Research, 2018)

Molecular cloning, antiserum preparation and expression analysis during head regeneration of $$\upalpha $$ α -crystallin type heat shock protein in Hydra vulgaris - Wen-Fang Dong; Hang Zhang; Ru-Meng Wang; Hong-Chun Pan (Journal of Genetics, 2018)

Application of Phragmites australis to remove phenol from aqueous solutions by chemical activation in batch and fixed-bed columns - Sheng-Li Shi; Jun-Ping Lv; Qi Liu; Fang-Ru Nan; Xiao-Yan Jiao; Jia Feng; Shu-Lian Xie (Environmental Science and Pollution Research, 2018)

Scopuquinolone B, a new monoterpenoid dihydroquinolin-2(1 H )-one isolated from the coral-derived Scopulariopsis sp. fungus - Xiao-Feng Mou; Xin Liu; Ru-Fang Xu; Mei-Yan Wei; Yao-Wei Fang; Chang-Lun Shao (Natural Product Research, 2018)

Role of early environmental enrichment on the social dominance tube test at adulthood in the rat - Wen-Yu Cao; Zhao-Lan Hu; Yang Xu; Wen-Juan Zhang; Fu-Lian Huang; Xiao-Qing Qiao; Yan-Hui Cui; Wei Wan; Xue-qin Wang; Dan Liu; Ru-Ping Dai; Fang Li; et al. (Psychopharmacology, 2017)

Early-Life Social Isolation-Induced Depressive-Like Behavior in Rats Results in Microglial Activation and Neuronal Histone Methylation that Are Mitigated by Minocycline - Hong-Tao Wang; Fu-Lian Huang; Zhao-Lan Hu; Wen-Juan Zhang; Xiao-Qing Qiao; Yan-Qing Huang; Ru-Ping Dai; Fang Li; Chang-Qi Li (Neurotoxicity Research, 2017)

NOX2 Mediated-Parvalbumin Interneuron Loss Might Contribute to Anxiety-Like and Enhanced Fear Learning Behavior in a Rat Model of Post-Traumatic Stress Disorder - Fang-fang Liu; Lin-dong Yang; Xiao-ru Sun; Hui Zhang; Wei Pan; Xing-ming Wang; Jian-jun Yang; Mu-huo Ji; Hong-mei Yuan (Molecular Neurobiology, 2016)

Application of high resolution SNP arrays in patients with congenital oral clefts in south China - TING-YING LEI; HONG-TAO WANG; FAN LI; YING-QIU CUI; FANG FU; RU LI; CAN LIAO (Journal of Genetics, 2016)

Peripheral Blood MicroRNA Expression Profiles in Alzheimer’s Disease: Screening, Validation, Association with Clinical Phenotype and Implications for Molecular Mechanism - Ru-Jing Ren; Yong-Fang Zhang; Eric B. Dammer; Yi Zhou; Li-ling Wang; Xiao-Hong Liu; Bei-Lei Feng; Guo-Xin Jiang; Sheng-Di Chen; Gang Wang; Qi Cheng (Molecular Neurobiology, 2016)

Molecular Design, Structural Analysis and Antifungal Activity of Derivatives of Peptide CGA-N46 - Rui-Fang Li; Zhi-Fang Lu; Ya-Nan Sun; Shi-Hua Chen; Yan-Jie Yi; Hui-Ru Zhang; Shuo-Ye Yang; Guang-Hai Yu; Liang Huang; Chao-Nan Li (Interdisciplinary Sciences: Computational Life Sciences, 2016)

Adsorption of Cd(II) by two variable-charge soils in the presence of pectin - Ru-hai Wang; Xiao-fang Zhu; Wei Qian; Min-hua Zhao; Ren-kou Xu; Yuan-chun Yu (Environmental Science and Pollution Research, 2016)

Neuroprotection of Sevoflurane Against Ischemia/Reperfusion-Induced Brain Injury Through Inhibiting JNK3/Caspase-3 by Enhancing Akt Signaling Pathway - Xiang-Ru Wen; Yan-Yan Fu; Hong-Zhi Liu; Jian Wu; Xiao-Ping Shao; Xun-Bao Zhang; Man Tang; Yue Shi; Kai Ma; Fang Zhang; Yi-Wen Wang; Hui Tang; et al. (Molecular Neurobiology, 2016)

Dormancy release of Cotinus coggygria seeds under a pre-cold moist stratification: an endogenous abscisic acid/gibberellic acid and comparative proteomic analysis - Zhi Jun Deng; Xiao Fang Hu; Xun Ru Ai; Lan Yao; Shi Ming Deng; Xin Pu; Song Quan Song (New Forests, 2016)

Silencing of dehydrin CaDHN1 diminishes tolerance to multiple abiotic stresses in Capsicum annuum L. - Ru-gang Chen; Hua Jing; Wei-li Guo; Shu-Bin Wang; Fang Ma; Bao-Gui Pan; Zhen-Hui Gong (Plant Cell Reports, 2015)

Effect of pectin on adsorption of Cu(II) by two variable-charge soils from southern China - Ru-hai Wang; Xiao-fang Zhu; Wei Qian; Yuan-chun Yu; Ren-kou Xu (Environmental Science and Pollution Research, 2015)

Invasive fungal infection in allogeneic hematopoietic stem cell transplant recipients: single center experiences of 12 years - Ji-min Shi; Xu-ying Pei; Yi Luo; Ya-min Tan; Ru-xiu Tie; Jing-song He; Wei-yan Zheng; Jie Zhang; Zhen Cai; Mao-fang Lin; He Huang (Journal of Zhejiang University-SCIENCE B, 2015)

Potent Antifouling Marine Dihydroquinolin-2(1H)-one-Containing Alkaloids from the Gorgonian Coral-Derived Fungus Scopulariopsis sp. - Chang-Lun Shao; Ru-Fang Xu; Chang-Yun Wang; Pei-Yuan Qian; Kai-Ling Wang; Mei-Yan Wei (Marine Biotechnology, 2015)

Changes in root morphology and physiology to limited phosphorus and moisture in a locally-selected cultivar and an introduced cultivar of Medicago sativa L. growing in alkaline soil - Jing-Wei Fan; Yan-Lei Du; Neil C. Turner; Bing-Ru Wang; Yan Fang; Yue Xi; Xiao-Ran Guo; Feng-Min Li (Plant and Soil, 2015)

Effect of microRNA-203 on tumor growth in human hypopharyngeal squamous cell carcinoma - Ru Wang; Jugao Fang; Hongzhi Ma; Lin Feng; Meng Lian; Fan Yang; Haizhou Wang; Qi Wang; Xiaohong Chen (Molecular and Cellular Biochemistry, 2015)

Compounds from marine-derived Verrucosispora sp. FIM06054 and their potential antitumour activities - Nie Yi-Lei; Wu Yun-Dan; Wang Chuan-Xi; Lin Ru; Xie Yang; Fang Dong-Sheng; Jiang Hong; Lian Yun-Yang (Natural Product Research, 2014)

(2R, 3S)-pinobanksin-3-cinnamate, a new flavonone from seeds of Alpinia galanga willd., presents in vitro neuroprotective effects - Ben Ru Xin; Jian Fang Liu; Jie Kang; Wing Ping Chan (Molecular & Cellular Toxicology, 2014)

Characterization of S-(+)-linalool synthase from several provenances of Cinnamomum osmophloeum - Yan-Liang Lin; Yi-Ru Lee; Wen-Ke Huang; Shang-Tzen Chang; Fang-Hua Chu (Tree Genetics & Genomes, 2014)

Synthesis, biological evaluation and molecular modeling studies of Schiff bases derived from 4-methylsalicylic acid as potential immunosuppressive agents - Ru Yan; Peng-Gang Liu; Zhi-Ming Zhang; Xian-Ying Fang; Xue-Wei Zhang; Jia-Li Deng; Hai-Liang Zhu (Medicinal Chemistry Research, 2013)

QTL mapping and correlation analysis for 1000-grain weight and percentage of grains with chalkiness in rice - JIAN-MIN BIAN; HUAN SHI; CUI-JUAN LI; CHANG-LAN ZHU; QIU-YING YU; XIAO-SONG PENG; JUN-RU FU; XIAO-PENG HE; XIAO-RONG CHEN; LI-FANG HU; LIN-JUAN OUYANG; HAO-HUA HE (Journal of Genetics, 2013)

Analysis of B-Class Genes NAP3L3 and NAP3L4 in Narcissus tazetta var. chinensis - Xiao-Fang Li; Jing Xu; Ru Yang; Lin-Yan Jia; Xin-Jie Deng; Li-Jun Xiong; Xue-Ping Zhang; Qi Fang; Wei Zhang; Yue Sun; Ling Xu (Plant Molecular Biology Reporter, 2013)

The prevalence of CD33 and MS4A6A variant in Chinese Han population with Alzheimer’s disease - Yu-Lei Deng; Li-Hua Liu; Ying Wang; Hui-Dong Tang; Ru-Jing Ren; Wei Xu; Jian-Fang Ma; Li-Ling Wang; Jun-Peng Zhuang; Gang Wang; Sheng-Di Chen (Human Genetics, 2012)

Polycyclic aromatic hydrocarbons in household dust near diesel transport routes - Chung-Yih Kuo; Heng-Chun Chen; Fang-Ching Cheng; Li-Ru Huang; Po-Shan Chien; Jing-Ya Wang (Environmental Geochemistry and Health, 2012)

An upstream regulatory element confers orientation-independent enhancement of the TSG101 promoter activity in transformed cells - Shih-Fang Hsu; Yih-Gang Goan; Hsien-Yu Tsai; Yi-Ru Lin; Rue-Tsuan Liu; Jiin-Tsuey Cheng (Molecular Biology Reports, 2012)

The Activation of NMDA Receptor–ERK Pathway in the Central Amygdala is Required for the Expression of Morphine-Conditioned Place Preference in the Rat - Fang Li; Xiao-Sheng Wang; Ru-Ping Dai; Jian-Yi Zhang; Xin-Fu Zhou; Wei Hao; Chang-Qi Li (Neurotoxicity Research, 2011)

Alternative splicing of the antitrypsin gene in the silkworm, Bombyx mori - Hui-fen Liu; Yi-nü Li; Ru Jia; Wei-zheng Cui; Zhi-mei Mu; Zhi-fang Zhang (Molecular Biology Reports, 2011)

Special Distribution of Polybrominated Diphenyl Ethers in Brain Tissues of Free-range Domestic Hens and Ducks from a Village near an Electronic Waste Recycling Site in South China - Zhong-Zhi Yang; Yong-Fang Li; Shan Fu; Xing-Ru Zhao (Bulletin of Environmental Contamination and Toxicology, 2011)

Genes expressed in Taiwania reproductive organs include two male-cone protein 1 precursor homologs - Fang-Hua Chu; Chieh-Wen Shen; Yi-Ru Lee; Shing-Rong Kuo (Journal of Plant Biochemistry and Biotechnology, 2011)

Stearoyl-CoA Desaturase (SCD) Gene Polymorphism in Goat Breeds - Chun-Lei Zhang; Xue-Yuan Gao; Ru-Ying Shao; Yan-Hong Wang; Xing-Tang Fang; Hong Chen (Biochemical Genetics, 2010)

Livin abrogates apoptosis of SPC-A1 cell by regulating JNKI signaling pathway - Yu-Sheng Chen; Hong-Ru Li; Ming Lin; Gang Chen; Bao-Song Xie; Neng-Luan Xu; Li-Fang Lin (Molecular Biology Reports, 2010)

Investigations on boron levels in drinking water sources in China - Ren-ji Xu; Xiao-ru Xing; Qun-fang Zhou; Gui-bin Jiang; Fu-sheng Wei (Environmental Monitoring and Assessment, 2010)

Analysis of the genetic diversity in Saccharum spontaneum L. accessions from Guangxi Province of China with RAPD-PCR - Ge-min Zhang; Yang-Rui Li; Wei-Zhong He; Hong He; Xi-Hui Liu; Huan-Zhong Song; Hai-Bin Liu; Ru-Cai Zhu; Wei-Kuan Fang (Sugar Tech, 2010)

Heterotrophic Photo Fermentative Hydrogen Production - RU YING LI; HERBERT H. P. FANG (Critical Reviews in Environmental Science and Technology, 2009)

Studying the Interaction of Pirarubicin with DNA and Determining Pirarubicin in Human Urine Samples: Combining Excitation -Emission Fluorescence Matrices with Second-order Calibration Methods - Hong-Yan Zou; Hai-Long Wu; Yan Zhang; Shu-Fang Li; Jin-Fang Nie; Hai-Yan Fu; Ru-Qin Yu (Journal of Fluorescence, 2009)

Strand compositional asymmetries in vertebrate large genes - Hai-Fang Wang; Wen-Ru Hou; Deng-Ke Niu (Molecular Biology Reports, 2008)

Glutathione S-transferases M1 and T1 polymorphisms and arsenic content in hair and urine in two ethnic clans exposed to indoor combustion of high arsenic coal in Southwest Guizhou, China - Guo-fang Lin; Hui Du; Ji-gang Chen; Hong-chao Lu; Jin-xiang Kai; Yun-shu Zhou; Wei-chao Guo; Xin-jiang Zhang; Da-ru Lu; Klaus Golka; Jian-hua Shen (Archives of Toxicology, 2007)

Effect of banning vancomycin analogue avoparcin on vancomycin‐resistant enterococci in chicken farms in Taiwan - Tsai‐Ling Lauderdale; Yih‐Ru Shiau; Hui‐Ying Wang; Jui‐Fen Lai; I‐Wen Huang; Pei‐Chen Chen; Hong‐Yi Chen; Shiow‐Suey Lai; Ya‐Fang Liu; Monto Ho (Environmental Microbiology, 2007)
Summary Avoparcin, a vancomycin analogue, was banned as a feed additive in Taiwan in 2000. A nationwide surveillance was conducted to study the prevalence of vancomycin‐resistant enterococci (VRE) on chicken farms between 2000 and 2003. Among the 1021 E. faecalis and 967 E. faecium isolates studied, resistance to tetracycline, erythromycin, high‐level aminoglycosides, ciprofloxacin and chloramphenicol either increased or remained high except vancomycin. The proportion of VRE decreased, between 2000 and 2003, from 13.7% (22/161) to 3.7% (11/299) for E. faecalis , and 3.4% (4/119) to 0% (0/300) for E. faecium . Only 8.8% (7/80) of the chicken farms surveyed harboured VRE in 2003 compared with 25% (15/60) in 2000. All VRE were resistant to tetracycline and erythromycin. All VRE possess the vanA gene but nearly all (79 of 83 isolates) were susceptible to teicoplanin, indicating VanB phenotype. Some clones were detected from different farms in various regions over the years. We conclude that the frequency of VRE in chicken farms decreased in association with a ban on avoparcin; and the continued presence of VRE may be due to the ability of some strains to persist in the farms, transfer of vancomycin resistance determinants or co‐selection by the continued use of other antibiotics.

Occurrence of foliar rot of pak choy and Chinese mustard caused by Rhizoctonia solani AG1-IB in China - Gen-Hua Yang; Hai-Ru Chen; Shigeo Naito; Jian-Yu Wu; Xia-Hong He; Chun-Fang Duan (Journal of General Plant Pathology, 2005)

Small heat-shock protein 22 mutated in autosomal dominant Charcot-Marie-Tooth disease type 2L - Bei-sha Tang; Guo-hua Zhao; Wei Luo; Kun Xia; Fang Cai; Qian Pan; Ru-xu Zhang; Fu-feng Zhang; Xiao-min Liu; Biao Chen; Cheng Zhang; Lu Shen; et al. (Human Genetics, 2005)

Estimation of atmospheric input of mercury to South Lake and Jingyue Pool - Feng-man Fang; Qi-chao Wang; Zhuang-wei Ma; Ru-hai Liu; Yu-hong Cao (Chinese Geographical Science, 2002)